Defects and stability of perovskite solar cells: a critical analysis. (11th January 2022) - Duan, Leiping; Uddin, Ashraf
Abstract : Metal halide perovskite solar cells (PSCs) continue to improve their power conversion efficiency to over 25.5%, which is at the same level as silicon solar cells. Abstract : Metal halide perovskite solar cells (PSCs) continue to improve their power conversion efficiency to over 25.5%, which is at the same level as silicon solar cells. The stability of perovskite cells is a challenging issue for the commercialization of this photovoltaic technology. The degradation of PSCs is mainly due to external environmental factors, such as oxygen, moisture, light, and heat. The degradation of PSCs by oxygen and moisture can be suppressed through the encapsulation of devices. However, encapsulation cannot reduce light and heat degradation under the operating conditions. In this Review, we mainly focus on the analysis of degradation mechanisms caused by light and heat. Compositional and interfacial engineering of perovskite material lattice sites are the most widely applied strategy to alleviate the degradation of PSCs. The improvements in PSC stability and device efficiency are also reviewed for defect passivation at charge transport layer/perovskite interfaces with various materials such as polymers, small molecules, quantum dots, ligands, charge-transporting layers dopants, and post-treatment of the perovskite film. This Review will help to understand the degradation mechanism of PSCs and improve their stability under illumination. We believe that this Review will help with the design the optimal PSCs for highly efficient and stable devices.